T-cadherin modulates adipogenic differentiation in mesenchymal stem cells: insights into ligand interactions - Sysoeva, Veronika; Semina, Ekaterina; Klimovich, Polina; Kulebyakin, Konstantin; Dzreyan, Valentina; Sotskaya, Ekaterina; Shchipova, Anna; Popov, Vladimir; Shilova, Alena; Brodsky, Ilya; Khabibullin, Nikita; Voloshin, Nikita; et al. (Frontiers in Cell and Developmental Biology, 2024)
IntroductionT-cadherin, a non-canonical member of the cadherin superfamily, was initially identified for its involvement in homophilic recognition within the nervous and vascular systems. Apart from its adhesive function, T-cadherin acts as a receptor for two ligands: LDL, contributing to atherogenic processes, and HMW adiponectin, a hormone with well-known cardiovascular protective properties. However, the precise role of T-cadherin in adipose tissue remains elusive. Previously, we generated Cdh13∆Exon3 mice lacking exon 3 in the Cdh13 gene, which encodes the T-cadherin protein, and characterized their phenotype.MethodsUsing wild-type (WT) and T-cadherin-deficient mice (Cdh13ΔExon3), we isolated and cultured mesenchymal stem cells to explore the role of T-cadherin in adipogenic differentiation. The experimental approaches employed include culturing cells under standard or adipogenic conditions, performing Oil Red O and Nile Red staining followed by quantitative analysis, conducting rescue experiments to reintroduce T-cadherin using lentiviral constructs in T-cadherin-deficient cells combined with automated adipocyte differentiation quantification via a neural network. Additionally, Western blotting, ELISA assays, and statistical analysis were utilized to verify the results.ResultsIn this study, we demonstrate for the first time that T-cadherin influences the adipogenic differentiation of MSCs. The presence of T-cadherin dictates distinct morphological characteristics in MSCs. Lack of T-cadherin leads to spontaneous differentiation into adipocytes with the formation of large lipid droplets. T-cadherin-deficient cells (T−/− MSCs) exhibit an enhanced adipogenic potential upon induction with differentiating factors. Western Blot, ELISA assays, and rescue experiments collectively corroborate the conclusion that T−/− MSCs are predisposed toward adipogenic differentiation. We carried out an original comparative analysis to explore the effects of T-cadherin ligands on lipid droplet accumulation. LDL stimulate adipogenic differentiation, while T-cadherin expression mitigates the impact of LDL on lipid droplet accumulation. We also examined the effects of both low molecular weight (LMW) and high molecular weight (HMW) adiponectin on lipid droplet accumulation relative to T-cadherin. LMW adiponectin suppressed lipid droplet accumulation independently of T-cadherin, while the absence of T-cadherin enhanced susceptibility to the suppressive effects of HMW adiponectin on adipogenesis.DiscussionThese findings shed light on the role of T-cadherin in adipogenic differentiation and suggest an interplay with other receptors, such as LDLR and AdipoRs, wherein downstream signaling may be modulated through lateral interactions with T-cadherin.